(untitled) (RPG学研究: Japanese Journal of Analog Role-Playing Game Studies, 2024)
Inclusive education and the development of empathy among educators are crucial for supporting students with disabilities. Deaf individuals, often facing unique challenges in mainstream educational settings, benefit from an educator's increased awareness and empathy. This study explores the impact of the role-playing game Sign: A Game About Being Understood (SIGN) on assistant language teachers' (ALTs) levels of empathy towards and awareness of deaf individuals in Japan.A mixed-method approach involving four ALTs from a rural prefecture in Japan was employed. Qualitative data were collected through pre- and post-intervention surveys with open-ended questions and a debrief-group interview session, while quantitative data were gathered using the Interpersonal Reactivity Index (IRI). The qualitative data were analysed using thematic analysis, focusing on three themes: Increased Empathy for and Awareness of the Deaf; Communication Challenges; and Game Mechanics.Participant responses indicated an increase in empathy and awareness of the deaf experience following the intervention. This study highlights the potential of experiential learning tools in teacher-training programs to foster more inclusive and supportive educational environments.